Implementation of the international obligations of states in the field of biodiversity conservation (based on the experience of the Russian Federation and the Republic of Iraq) - G.R. Shaikhutdinova; S.Kh. Jaber (Ученые записки Казанского университета: Серия Гуманитарные науки)
The national legislations of the Russian Federation and the Republic of Iraq have been compared in the light of the fulfillment of international obligations associated with the ratification of the 1992 United Nations Convention on Biological Diversity. It has been concluded that both countries face urgent environmental problems that can be partially solved by implementation of the Convention. It has been revealed that the states implement their international obligations by consistent development of a legal (legislative) and institutional framework and by participation in the Convention's monitoring mechanism through the submission of national reports on preservation of biological diversity. In addition, it has been suggested for Iraq to adopt a positive experience of the Russian Federation in an integrated approach to the preservation of biological diversity based on the development of a number of branches of national legislation, including forest, water, land, and subsoil legislation, as well as legislation on wildlife protection. Russia can assimilate the experience of Iraq in creating conservation areas and national reserves in wetlands and assigning the status of UNESCO cultural heritage sites to them. Creating conservation areas and national reserves is one of the priorities for the Russian Federation's policy in the sphere of environmental protection.